Politik dan Pesantren Studi Kasus Pesantren Darul Arafah Raya - Kuperju Syahputra Ritonga (Kampus Akademik Publiser, 2025)
This writing is motivated by the relationship between politics and Islamic boarding schools, with a focus on the case study of Darul Arafah Raya Islamic Boarding School. Islamic boarding schools, as traditional Islamic educational institutions, play a strategic role in shaping the character and religious understanding of society. In the Indonesian context, where political dynamics often interact with religious values, Islamic boarding schools function not only as social entities that can influence and be influenced by political changes. The methodology used in this study is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. Research related to politics and Islamic boarding schools shows that Darul Arafah Raya Islamic Boarding School has a dual role as a place of religious education and as an arena for political discourse. The boarding school leaders are involved in local political activities, both through supporting leadership candidates and educating students about the importance of participation in the democratic process. Pesantren Darul Arafah Raya plays an important role in the local political context, but this needs to be balanced with efforts to maintain the integrity of religious education. The role of this pesantren also strengthens the curriculum that promotes moral values and ethical leadership in politics and encourages active participation by students.